Prognostic implications of T stage in different pathological types of colorectal cancer: an observational study using SEER population-based data - Jiwei Wang; Wenqiang Li; Nan Yao; Ning Duan; Jun Qu; Hongyuan Chu; Xinyu Niu; Guoyong Yu (BMJ Open, 2024)
Objectives Colorectal cancer (CRC) encompasses a spectrum of pathological types, each exhibiting distinct biological behaviours that challenge the conventional T-staging system’s predictive efficiency. Thus, this study aims to explore the prognostic significance of the T stage across various CRC pathological types, seeking to unravel insights that could enhance prognostic assessment in this complex disease.Study design We performed a retrospective analysis using the Surveillance, Epidemiology, and End Results (SEER) database for primary CRC cases from 2010 to 2017.Setting The SEER database, comprising data from various US regional and state cancer registries, identified 39 321 patients with CRC. Our analysis focused on the three most common CRC pathological types: adenocarcinoma (AC), mucinous adenocarcinoma (MC) and signet ring cell carcinoma (SR).Primary outcome measures The study used Cox regression models to evaluate how different pathological characteristics impact mortality risk in patients with CRC. Time-dependent receiver operating characteristic curves were also applied to assess the prognostic accuracy of various tumour node metastasis (TNM)/non-mucinous (NM) stages.Results We observed significant associations between T stage and mortality risk for patients with AC and MC. Notably, in comparison to those at T1 stage, patients with AC in the T4 stage demonstrated a 2.01-fold increase in mortality risk (HR=2.01, 95% CI: 1.89 to 2.15), while patients with MC at T4 stage showed a 1.42-fold increase (HR=1.42, 95% CI: 1.03 to 1.97). However, within the SR group, T stages did not independently impact survival, showing no significant distinction (HR=1.07, 95% CI: 0.59 to 1.95). Intriguingly, the traditional TNM staging systems demonstrated limited discriminatory power in predicting prognosis for patients with SR when compared with the more innovative NM staging systems.Conclusions This study uncovers important insights about the prognostic significance of the T stage in different types of CRC, highlighting the need for personalised assessments based on specific histological subtypes.